Bilateral lacrimal sac mucocele with punctal and canalicular atresia - Ong, C.A.; Prepageran, Narayanan; Sharad, G.; Luna, D. (Malaysian Medical Association, 2005)
Congenital absence of lacrimal puncta may be an isolated finding or associated with other developmental abnormality. Nasolacrirnal ducts can be absent thus predisposing to the formation of a congenital lacrimal mucocele. Punctal and canalicular agenesis is very rare. Four percent of new patients attending the lacrimal clinic at Moorfields Eye Hospital, London, UK. from 1981 to 1990 inclusive were diagnosed to have this condition. We describe a case of bilateral congenital absence of lacrimal puncta with lacrimal mucocele. Combined surgery was carried out by Ophthalmologist and Otolaryngologist with successful results.